Avaliação farmacológica no sistema nervoso central de um novo derivado piperazínico LQFM 104 - Rodrigues, Oscar Romero Lopes (2015)
The Laboratório de Química Farmaceutica Medicinal designed and synthesized a new piperazine derivative tert-butyl 4-((1-phenyl-1H-pyrazol-4-yl)methyl)piperazine-1-carboxylate (LQFM104) based on molecular framework of clozapine. This study aimed the pharmacological evaluation in the central nervous system of the LQFM104. Treatment with LQFM104 at doses of 25 , 50 or 100 μmol/kg (p.o.) in the open-field test did not alter in animals the number of grooming behavior, the number of fecal boluses, the total number of crossings, immobility time, number of rears, the percentage of crossings in the central area and the time spent in the center. None of groups of doses tested with LQFM104 was able to change the time spent in the chimney test. In pentobarbital-induced sleep test, the treatment with LQFM104 25, 50 or 100 μmol/kg (p.o.) did not affect sleep latency, while the sleep duration has increased by 65%, 64.4% and 78.6% respectively compared to the control group treated orally with vehicle 10 ml/kg (28.8 ± 2.9 minutes). In the standardization of apomorphine-induced climbing test, the treatment with haloperidol at dose of 2.6 μmol/kg was able to reduce the climbing behavior in 97.8%, whereas clozapine at dose of 45 μol/kg, has reduced this behavior in 78 % when compared to control (16.87 ± 2.8). The LQFM104 50 or 200 μmol/kg (p.o.) was not able to reduce the climbing behavior. In the forced swimming test just LQFM104 50 μmol/kg (p.o.) was able to reduce the immobility time in 19.8% compared to the control group ( 263.2 ± 6.7 seconds) and increased the latency to immobility in 43%, compared with the control ( 70.6 ± 6.5 seconds). Similarly, in the tail suspension test, only the LQFM104 50 μmol/kg (p.o.) increased immobility time (32.1%) compared to the control (216.1 ± 13.2 seconds). The LQFM104 50 μmol/kg (p.o.) had their antidepressant-like effects completely reversed by blocking treatment with PCPA and NAN-190. And the quantification of brain-derived neurotrophic factor the LQFM104 50 μmol/kg (p.o.) did not change these levels. The results with LQFM104 in the open-field test indicated no changes in spontaneous locomotor activity and showed no anxiogenic activity. The chimney test did not reveal impairment in motor coordination. The pentobarbital-induced sleep test increased sleep duration without reducing the latency, thus suggesting a sedative action. The forced swimming test and the tail suspension test confirmed for LQFM104 50 μmol/kg (p.o.) an antidepressant activity in mice. The blockade with NAN-190 and PCPA suggests the involvement of serotonergic system and 5-HT1A receptor.